Study of supercapacitors with a double electrical layer based on activated carbon materials - Budzulyak, I.M.; Kovalyuk, Z.D.; Motsnyi, F.V.; Orletskyi, V.B. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
It is proposed ecologically pure technology to obtain activated carbon. On the base of this carbon the supercapacitors were manufactured. Their characteristics were determined and compare with analogs obtained using ecologically dangerous materials.